An evaluation of interventions within a Growth Through Nutrition project aimed at enhancing optimal nutrition and water, sanitation and hygiene (WASH) and nutrition practices among nutritionally most vulnerable households (MVHHs) in Ethiopia. - Cherinet Abuye; Daniel Abbott; Lioul Berhanu; Adam Bailes; Rachel Holtzman (PLoS ONE)
Despite a downward trend, Ethiopia still faces significant challenges with high rates of stunting and acute malnutrition in children. To tackle these issues, the Feed the Future Ethiopia Growth Through Nutrition Activity, a USAID-funded project aligned with Ethiopia's National Nutrition Program, was executed from 2016 to 2023. This initiative aimed to enhance nutrition for women and young children across six regions through multisectoral interventions. Annual surveys conducted in 2017, 2018, and 2020 evaluated the impact of livelihood support and Water, Sanitation, and Hygiene (WASH)-focused social behavior change communication (SBCC) on vulnerable households with children under two. The results showed significant improvements in child nutrition. Dietary diversity among children increased from 12% to 34% (p<0.001), and the percentage of children receiving a minimal acceptable diet rose from 12% to 30.7% (p<0.001). Women's dietary diversity also improved markedly, from 2% to 16% (p<0.001). Handwashing practices saw improvements, with the proportion of households having handwashing facilities rising from 14% to 31% (p<0.001), and the adherence to critical handwashing moments increased from 16% to 23%. However, challenges in water treatment and latrine use persisted, with less than 25% improvement. The findings suggest that integrating livelihood support with SBCC interventions can positively enhance nutritional outcomes. Continued focus on these strategies is recommended to further support vulnerable households.